Analysis of The Effects Debt Capital, Equity Capital on Residual Income and It Is Impacts on Amount Coperative Member - Adih Supriadi (Jurnal Sains Sosio Humaniora, 2021)
The researchs is find out the effects of DC and EC on residual income (SHU) and it is impacts on amount coperative member. The researchs is descriptif quantitativ, the population used as the units of researchs analyzis is a coperative in the city of Tangsel with criteria coperatives that have many business units, and always hold annual member meetings for the last five consecative years, namely 2016 to 2020, as for the numbers of coperatives that will be sampled in this researchs are fifty coperatives. This research uses the methode asociative causall analitycal which mean a causall relationships wherein the variables X would effects variables Y and variables Y would effects variables Z. This methode is find out the relationships among two or more variables, by explining, predicting along controling symptoms. From researchs result it was found that DC partial significants effects on residual income, withal determinations coefficients is 72,29 %, the rest 27,71 % influence by others factor. EC partiall significants effects on residual income, withal coefficients of determinations is 74,67 %, the rest 25,33 % influence by others factor. DC and EC simultaneouly significants effects on residual income, withal coeficient of determinations is 81,81 %, the rest 18,19 % influence by others factor. Residual income partial significants effects on amount coperative member with a coeficient of determinations is 41,82 %, the rest 58,18 % influence by others factor.